Preparation and physicochemical characterization of a biodegradable chitosan/carboxymethyl cellulose hydrogel synthesized in NaOH/urea medium - Johanna Morales; Allan Vásquez; Irma Patricia Orellana Catalán (PLoS ONE, 2026)
The use of super absorbent polymers in agriculture for water and fertilizers retention in soils has become popular with the increasing need for resource optimization. The objective of the present study was to use chitosan extracted from shrimp shell waste and reagent grade carboxymethylcellulose to synthesize a biodegradable super absorbent polymer with potential use for soil amendment in agriculture. The super absorbent polymer was synthesized using epichlorohydrin as a crosslinking agent in an alkaline NaOH/urea medium. The structure of the product was confirmed by FTIR and TGA. The polymer was found to be biodegradable with a progressive weight loss percentage reaching 79.1% after 14 days. An adsorption ratio of 15.8 and 17.2 was obtained for water and 22% w/v urea solution, respectively, so the product was categorized as super absorbent in both conditions. In addition, after two hours in the medium, absorption percentages of 48.3% were recorded for water and 22% w/v for urea solution. The reported method is effective for synthesizing a biodegradable super absorbent polymer with potential use for soil amendment and susceptibility to pH changes for both adsorption equilibrium and over time adsorption.